Monsoon intensification in East Asia triggered the evolution of its flora - Ye, Jun-Wei; Tian, Bin; Li, De-Zhu (Frontiers in Plant Science, 2022)
Introduction East Asia (EA), which falls within the region of the Asian monsoon that is composed of the East Asia monsoon (EAM) and the Indian monsoon (IM), is known for its high species diversity and endemism. This has been attributed to extreme physiographical heterogeneity in conjunction with climate and sea-level changes during the Pleistocene, this hypothesis has been widely proven by phylogeographic studies. Recently, dated phylogenies have indicated that the origins (stem age) of the flora occurred after the Oligocene–Miocene boundary and are related to the establishment of the EAM. Methods Hence, this study further examined whether the strengthening of the monsoons triggered floral evolution via a meta-analysis of the tempo-spatial pattern of evolutionary radiation dates (crown ages) of 101 endemic seed plant genera. Results Taxonomic diversification began during the late Eocene, whereas the accumulated number of diversifications did not significantly accelerate until the late Miocene. The distribution of the weighted mean and the average divergence times in the EAM, IM, or transitional regions all fall within the mid-late Miocene. Fossils of the Tertiary relict genera are mostly and widely distributed outside EA and only half of the earliest fossils in the EA region are not older than Miocene, while their divergence times are mostly after the late Miocene. The pattern of divergence time of monotypic and polytypic taxa suggest the climatic changes after the late Pliocene exert more influence on monotypic taxa. Discussion The two key stages of floral evolution coincide with the intensifications of the EAM and IM, especially the summer monsoon which brings a humid climate. An integrated review of previous studies concerning flora, genus, and species levels further supports our suggestion that monsoon intensification in EA triggered the evolution of its flora.